Study on Feasibility of The Using Hemp Firbre into a Tile Composite Process - Keokangdong, Sengphet; Houngbounyuang, Sayphone; Laungvilath, Hong; Vongvilay, Saythong (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The aim of the present study is to introduce natural hemp ﬁbre as reinforcement in the preparation of roof tile green composites. The roof tile green composite was prepared from mixing of the hemp fibre and epoxy resin. Epoxy resin was mixed between (A: B) with ratio (2: 1) by stirring of slurry until homogenous and then was purred into the mould (200 mm x150 mm 3mm) with amount of hemp fibre as such (5, 10, 20, 25 wt.%) then were pressed and leave in the room temperature for 24 hrs. Density, water absorption, and Mechanical properties were investigated. The results show that, the density of samples was increased during increasing of hemp content (5 - 25 wt.%), in opposite the water absorption decreased by adding of hemp contents. The mechanical properties of composites were also increased when increasing of fibre contents. From the results of study can be concluded with all properties were increased with increasing of hemp fibres content in the green biocomposite samples.